Tax incentives and capital spending - Fromm, Gary; Brookings Institution (Washington, Brookings Institution, 1971)
This book examines the effect of the investment tax credit and accelerated depreciation on level of investment expenditures.
This is a collection of papers
Bibliographical reference
MF23/01/2019
Loans
Keywords: Investment tax credit; Capital investments; Tax incentives